Corybas hamiguitanensis (Orchidaceae), a new species from a UNESCO world heritage site in the Philippines - Tandang, Danilo N.; Docot, Rudolph Valentino A.; Galindon, John Michael; Reyes Jr., Tomas; Tadiosa, Edwin R.; Tandang, Sue Dixie A.; Moran, Cecilia B.; Bustamante, Rene Alfred Anton (Phytotaxa, 2023)
A new species of helmet orchid, Corybas hamiguitanensis, is herein described and illustrated. It is the first species of the genus recorded in Mindanao Island, Philippines. This novel species occupies varied climatic zones along different altitudinal gradients ranging from lowland evergreen rainforest up to the mossy forest of Mount Hamiguitan Range Wildlife Sanctuary.